Comprehensive evaluation of military training-induced fatigue among soldiers in China: A Delphi consensus study - Ruan, Yi; Song, Shang-jin; Yin, Zi-fei; Wang, Man; Huang, Nian; Gu, Wei; Ling, Chang-quan (Frontiers in Public Health, 2022)
Objective Military training-induced fatigue (MIF) often results into non-combat attrition. However, standard evaluation of MIF is unavailable. This study aimed to provide credible suggestions about MIF-evaluation. Methods A 3-round Delphi study was performed. The authority of the experts was assessed by the authority coefficient (Aa). In round 1, categories of indicators were collected via anonymous survey of experts, then potential indicators were selected via literature search. In round 2, experts should evaluate the clinical implication, practical value, and importance of each potential indicators, or recommend new indicators based on feedback of round 1. Indicators with recommendation proportions ≥ 70% and new recommended indicators would be included in round 3 to be rated on a 5-point Likert scale. “Consensus in” was achieved when coefficient of concordance (Kendall's W) of a round was between 0.2 and 0.5 and the coefficient of variation (CV) of each aspect for an indicator was < 0.5. If round 3 could not achieve “consensus in,” more rounds would be conducted iteratively based on round 3. Indicators included in the recommendation set were ultimately classified into grade I (highly recommended) or grade II (recommended) according to the mean score and CV of the aspects. Results Twenty-three experts participated with credible authority coefficient (mean Aa = 0.733). “Consensus in” was achieved in round 3 (Kendall's W = 0.435, p < 0.001; all CV < 0.5). Round 1 recommended 10 categories with 73 indicators identified from 2,971 articles. After 3-round consultation, consensus was reached on 28 indicators focusing on the cardiovascular system (n = 4), oxygen transport system (n = 5), energy metabolism/metabolite level (n = 6), muscle/tissue damage level (n = 3), neurological function (n = 2), neuropsychological/psychological function (n = 3), endocrine function (n = 3), and exercise capacity (n = 2). Among these, 11 indicators were recommended as grade I: basic heart rate, heart-rate recovery time, heart rate variability, hemoglobin, blood lactic acid, urine protein, creatine kinase, reaction time, Borg Rating of Perceived Exertion Scale, testosterone/cortisol, and vertical jump height. Conclusion This study developed a reliable foundation for the comprehensive evaluation of MIF among soldiers.